Visible/infrared refractive index and phonon properties of GaN films grown on sapphire by hollow-cathode plasma-assisted atomic layer deposition - ALEVLİ, MUSTAFA (A V S AMER INST PHYSICS, 2019)
Using Raman spectroscopy and spectroscopic ellipsometry, the authors report on the refractive index and optical phonon modes of GaN layers with thicknesses from 6.57 to 84.35 nm, grown on sapphire (0001) substrates by hollow-cathode plasma-assisted atomic layer deposition at low temperature (200 degrees C). The crystalline nature of the GaN films was confirmed by Raman spectroscopy and spectroscopic ellipsometry. The dispersion of the refractive index of GaN films in the UV-visible and infrared part of the spectrum is determined. The finding of this work indicates that the film thickness has important effects on the refractive index in the wavelength range of 300-1000 nm. On the other hand, the refractive index in the infrared region does not obviously change with increasing thickness. The authors compare the results of infrared ellipsometry with Raman spectra. They have identified E-1(TO), E-1(LO), A(1)(LO), and E2High phonon modes. The dependencies of their frequencies on the stress state of GaN films were analyzed and discussed. Published by the AVS.
Keywords: THIN-FILMS; OPTICAL CHARACTERIZATION; DIELECTRIC FUNCTION; HEXAGONAL GAN; EPITAXY; INN; ALN